EVALUATION OF ENZYME PRODUCTION BY CANDIDA SPP. ISOLATED FROM PATIENTS WITH ONYCHOMYCOSIS IN HUE CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the production of virulence-associated enzymes, including protease, phospholipase, and lipase, in Candida albicans, Candida tropicalis and Candida parapsilosis isolated from patients with onychomycosis.Methods: A cross-sectional descriptive study was conducted on 90 Candida isolates obtained from patients diagnosed with Candida onychomycosis. Species identification was performed using carbohydrate assimilation tests with the API 20C system (bioMérieux–Vitek, France). Protease, phospholipase, and lipase activities were assessed using the spot inoculation method on specific enzyme-detecting media, following previously published protocols.Results: The overall proportions of Candida spp. exhibiting protease, lipase, and phospholipase activity were 82.2%, 77.8%, and 36.7%, respectively. Both C. albicans and C. tropicalis demonstrated very high levels of protease and lipase activity (100% and 96.7%, respectively), whereas C. parapsilosis predominantly showed absent or low enzymatic activity; this difference was statistically significant (p
Keywords: Candida spp., enzyme production, onychomycosis.